Impact of Synthesis Method and Metal Salt Precursors on the CO2 Adsorption Performance of Layered Double Hydroxides Derived Mixed Metal Oxides - Cheah, Li Anne; Manohara, G. V.; Maroto-Valer, M. Mercedes; Garcia, Susana (Frontiers in Energy Research, 2022)
Since 1990s, Mg-Al Layered Double Hydroxides (LDHs) based Mixed Metal Oxides (MMOs) have emerged as promising CO2 capture sorbents. Despite the numerous attempts to improve these materials, the impact of synthesis method and employed metal salt precursors on the properties of LDHs and MMOs remains unknown. To address this gap, the present study investigated how two common synthesis methods, i.e., co-precipitation and urea hydrolysis, and two different salt precursors, i.e., metal chlorides and metal nitrates, affected the physical properties of LDHs and CO2 capture performance of derived MMOs at intermediate temperature (200 ˚C). The true chemical composition of LDH phase was confirmed by the lattice parameter “a”, which reveals the Mg/Al ratios at the octahedral layers. The impact of synthesis methods and metal salt precursors was evaluated in terms of synthesis efficiency metrics, e.g., synthesis yield, purity, and percentage of unreacted reactants and studied their relationship with the CO2 adsorption behaviour of MMOs in different aspects, e.g., adsorption capacities, kinetics and cyclic stability. Pure MgO was used as a reference to assess the cyclic stability of MMOs sorbents. It was found that the LDHs synthesized by the co-precipitation method are superior in terms of high synthesis yields ( 100 %), good LDH purity, high adsorption capacities and kinetics; whereas the LDHs synthesized with urea hydrolysis method are better in terms of cyclic stability but tends to have low synthesis yields (54 – 81 %) and LDH purity (contains large amount of amorphous impurities Al-based hydroxides).